Too big to care or "too big to share": The Digital Services Act and the consequences of reforming intermediary liability rules - Fredrik Erixon (European Centre for International Political Economy (ECIPE), 2021)
This paper reviews the Digital Services Act (DSA), a package of new rules for platforms proposed by the European Commission late last year. The paper takes stock of current and future situations for rules on content moderation and takedowns, and discusses how the DSA addresses the balance between the desired culture of openness online, on the one hand, and more pressures to take down not just illegal but harmful and objectionable content, on the other hand. The DSA introduces a few new transparency rules that follow previous codes of conduct: they are straightforward and desirable. However, it also brings in new know-your-customer rules and exacerbate the ambiguity surrounding the definition of illegal content. These types of rules will most likely have the effect that platforms will minimize risk even more by taking down more content that is legal. Moreover, there is a risk that the DSA will create new access barriers to platforms - with the result of making it difficult for smaller sellers to engage in contracts on platforms. New regulatory demands to monitor and address "systemic risks" will likely have the same effect: platforms will reduce their exposure to penalty risks by taking down and denying access for content that is legal but associated with risks.
Keywords: 330